Anger, Anxiety, and Selective Exposure to Terrorist Violence. (November 2021) - Huddy, Leonie; Smirnov, Oleg; Snider, Keren L. G.; Perliger, Arie
We examine the political consequence of exposure to widely available video content of terror violence. In a two-wave survey of Americans, we assess who is exposed to, and seeks out, terror-related video content in the first wave and then observe who decides to watch raw video footage of the Boston marathon terror attack in the second. We focus centrally on anxiety and anger as differing emotional reactions to the threat of terrorism and document their influence on exposure to terror violence. Anxiety generates avoidance of violent terror content whereas anger increases its consumption. Moreover, we find that anger increases exposure to violent terror content and in addition enhances support for punitive and retaliatory anti-terrorism policy. We discuss the implications of our findings for the broader dynamics of terrorist violence and the emotional basis of selective news exposure.